The Relation of Rational Actions with Positive Thinking in Socio-Economic Resilience Efforts During The COVID-19 Pandemic by Malioboro Street Vendors - Atri Putri Khoirun Nur P; Mahendra Wijaya; Ahmad Zuber (International Journal of Social Service and Research, 2022)
Rational action is an action that has subjective meaning or meaning in determining what to do, what to think about the type of work, which is able to give better hope, by taking effective actions to achieve the goal of social economic resilience during the covid pandemic 19. In the midst of the imposition of restrictions on community activities, it has an impact on various sectors of people's lives both socially and economically, one of which is a decrease in the level of income felt by street vendors, due to the impact of the enforcement of operating hours and restrictions on community activities outside the home for activities , by doing positive thinking can give enthusiasm, trust, confidence in his ability to deal with problems effectively, by providing actions in the form of efforts from traders as actors in the informal sector, one of which is a trader. street vendors in the Maliaboro area. The research method used in this study is a qualitative naturalistic inquiry. The purpose of this research is how to act rationally with positive thinking in the effort of socio-economic resilience during the Covid pandemic by Malioboro Street Vendors. In the recovery process, all street vendors have carried out their mandatory vaccines, used masks, washed their hands, and kept their distance. In the process of creativity, they promote their products through online shoppe, tokopedia, and Instagram media. The conditions felt by Maliaboro street vendors are not only rational actions in economic resilience, they must also make efforts to overcome the risks faced in order to be able to survive in the PPKM policy period.